2020
DOI: 10.1093/imrn/rnaa274
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Singularity Theory for Random Polynomials

Abstract: Motivated by Hilbert’s 16th problem we discuss the probabilities of topological features of a system of random homogeneous polynomials. The distribution for the polynomials is the Kostlan distribution. The topological features we consider are type-$W$ singular loci. This is a term that we introduce and that is defined by a list of equalities and inequalities on the derivatives of the polynomials. In technical terms a type-$W$ singular locus is the set of points where the jet of the Kostlan polynomials belongs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…This is the content of Corollary 5.3 which will use the estimates on the distance to the real discriminant Σ d proved in Section 3.2. In the case of Kostlan polynomials similar results can be found in [5,Proposition 3] and[3, Theorem 7]. Let s ∈ RH 0 (X, ⊕ m i=1 L d i ) \ Σ d be a real section (see Definition 3.1 for the definition of the real discriminant Σ d ).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…This is the content of Corollary 5.3 which will use the estimates on the distance to the real discriminant Σ d proved in Section 3.2. In the case of Kostlan polynomials similar results can be found in [5,Proposition 3] and[3, Theorem 7]. Let s ∈ RH 0 (X, ⊕ m i=1 L d i ) \ Σ d be a real section (see Definition 3.1 for the definition of the real discriminant Σ d ).…”
supporting
confidence: 56%
“…In our case, Theorem 1.4 is a consequence of the low degree approximation property given by Theorem 1.2. This has already been observed first in the case of Kostlan complete intersections in P n in [3,5] and then in the case of real hypersurfaces in a real algebraic variety in [2].…”
Section: Introductionmentioning
confidence: 55%
“…We finish with the following theorem, similar in flavour to [28, Proposition 3] and [11,Theorem 7], where it was shown that the distance of a polynomial tuple to polynomial tuples with singularities bounds the distance of this polynomial to C 1 -functions with singularities.…”
Section: Complexity Of the Plantinga-vegter Algorithmmentioning
confidence: 87%
“…The meaning of "singular point" depends on the situation, but in general it is a point p ∈ M where the section satisfies some condition involving its derivatives. A general model for that (the same proposed in [25] and [7]) is to consider a subset W ⊂ J r E of the bundle of r jets (if the derivatives involved are of order less than r) of sections of E (see [17] for a definition of the space of jets) and call singular points of class W those points p ∈ M such that the r th jet of X at p belongs to W . Examples are:…”
Section: Semialgebraic Singularitiesmentioning
confidence: 99%